Layanan Konseling Kelompok untuk Menurunkan Perilaku Agresif Siswa Disekolah - Suryanto Suryanto; Arifin Nur Budiono; Yurike Kinanthy Karamoy (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2018)
Outreach Counseling Group to lose the aggressive behaviour of the students In Class VII A MTs Al - Ma'arif Wuluhan Jember Years 2017/2018 Lessons. with the respondents examined as many as 26 students. Data collection methods used are observation and question form, data analysis used are descriptive data analsis. Based on the results of preliminary observations by the now major data and obtain the percentage by number of self concept of students in all schools amounted to 73%, after being given the action cycle I aggressive behavior of students in schools has decreased by a large percentage 42%, having resumed on cycle II level of aggressive behavior has decreased with a large percentage of 20%. Thus the conclusion, delivery of counselling services group indicates that aggressive behavior of students in schools has decreased. Research activities have been successfully categorized karna percentages under the indicators of success that has been set by 25% percentage of aggressive behavior in schools. Thus with the granting of group counseling services can reduce aggressive behavior of students in Class VII A in MTs Al - Ma'arif Dukuh Dempok Wuluhan school year 2017/2018.  Keywords: Group Counseling, Aggressive Behavior